Synthesis and Characterization of High Temperature Properties of YBa2Cu3O6+δ Superconductor as Potential Cathode for Intermediate Temperature Solid Oxide Fuel Cells - Grassi, Joaquín (2021)
YBa2Cu3O6+δ (YBC) oxygen deficient perovskite was synthesized by an auto-combustion method and was studied as potential cathode for Intermediate Temperature Solid Oxide Fuel Cell (IT-SOFC). Synchrotron X-ray thermodiffraction in air shows a phase transition from orthorhombic Pmmm to tetragonal P4/mmm space groups at ~ 425 °C. The chemical compatibility with Ce0.9Gd0.1O1.95 (GDC) electrolyte was investigated in air where certain reactivity wasobserved above 800 °C. However, the main phase is Ba(Ce1-xYx)O3, a good ionic conductor. The catalytic performance in air was obtained by electrochemical impedance spectroscopy (EIS) measurements on YBC/GDC/YBC symmetrical cells. The area specific resistance (ASR) values change from 13.66 to 0.14 Ω cm2 between 500 and 800 °C, with activation energy (Ea) of 0.41 eV. The results suggest potential applications of YBC as IT-SOFC cathode.